Optimization of DNA extraction for RAPD and ISSR analysis of Arbutus unedo L. leaves - Sá, Olga (2014)
Genetic analysis of plants relies on high yields of pure DNA. For the strawberry tree (Arbutus unedo) this represents a great challenge since leaves can accumulate large amounts of polysaccharides, polyphenols and secondary metabolites, which co-purify with DNA. For this specie, standard protocols do not produce efficient yields of high-quality amplifiable DNA. Here, we present for the first time an improved leaf-tissue protocol, based on the standard cetyl trimethyl ammonium bromide protocol, which yields large amounts of high-quality amplifiable DNA. Key steps in the optimized protocol are the addition of antioxidant compounds—namely polyvinyl pyrrolidone (PVP), 1,4-dithiothreitol (DTT) and 2-mercaptoethanol, in the extraction buffer; the increasing of CTAB (3%, w/v) and sodium chloride (2M) concentration; and an extraction with organic solvents (phenol and chloroform) with the incubation of samples on ice. Increasing the temperature for cell lyses to 70 °C also improved both DNA quality and yield. The yield of DNA extracted was 200.0 ± 78.0 μg/μL and the purity, evaluated by the ratio A260/A280, was 1.80 ± 0.021, indicative of minimal levels of contaminating metabolites. The quality of the DNA isolated was confirmed by random amplification polymorphism DNA and by inter-simple sequence repeat amplification, proving that the DNA can be amplified via PCR.